Enhancing mechanical properties and corrosion resistance through coating SiC during wire arc additive manufacturing of 2205 duplex stainless steel - Haidong WANG; Shuang XU; Jili LIU; Xide LI; Dawei QIU (Hanjie xuebao)
To address the issues of low mechanical strength, high anisotropy and reduced corrosion resistance in wire and arc additive manufacturing (WAAM) duplex stainless steel caused by coarse grains and columnar crystal epitaxial growth, SiC particles were introduced. In this paper, SiC particles with different particle sizes (100 and 1 000 nm) were prepared as ethanol-based suspensions containing 0, 2% and 10wt.% during the surfacing process of WAAM 2205 duplex stainless steel, which were added to the welding pool layer by layer. The results show that after adding SiC particles, the two phases ratio of WAAM 2205 duplex stainless steel was more balanced, the coarse columnar crystal structure along the stacking direction become a finer equiaxed crystal structure, and the texture intensity of grain orientation was significantly reduced. As result, the yield strength and ultimate tensile strength of the samples coated with SiC particles in the printing direction and stacking direction were significantly improved. The yield strength of the samples coated with 100 nm 10% SiC particle ethanol suspension in the printing direction and stacking direction increased by 7.75% and 15.51%, respectively, and the tensile strength increased by 8.96% and 17.16%, respectively. It is worth noting that the anisotropy of yield strength and tensile ultimate strength decreased from 7.50% and 7.75% of the uncoated sample to 0.85% and 0.81%, respectively, and the mechanical properties improved significantly. Noteworthy, the anisotropy of the yield strength and tensile ultimate strength decreased to 0.85% and 0.81%, respectively, compared with 7.50% and 7.75% of the uncoated sample. And the mechanical properties were significantly improved. Meanwhile, due to the increase of nucleation sites of oxide film caused by grain refinement, the charge transfer resistance of the sample coated with 100 nm 10% SiC particle ethanol suspension in 3.5% NaCl solution was 256.79% of that of the uncoated sample, and the corrosion resistance was also improved. This paper provides a reference for WAAM printing components with excellent comprehensive performance.